2020
DOI: 10.3390/nano10081505
|View full text |Cite
|
Sign up to set email alerts
|

The Emerging Role of Cold Atmospheric Plasma in Implantology: A Review of the Literature

Abstract: In recent years, cold atmospheric plasma (CAP) technologies have received increasing attention in the field of biomedical applications. The aim of this article is to review the currently available literature to provide an overview of the scientific principles of CAP application, its features, functions, and its applications in systemic and oral diseases, with a specific focus on its potential in implantology. In this narrative review, PubMed, Medline, and Scopus databases were searched using key words like “co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 74 publications
0
36
0
Order By: Relevance
“…Very few studies have been published in the literature on the effects of a combined treatment of CAP with other devices. In a recent review [18], only 17 in vitro studies and 5 in vivo on animal models investigating the effects of CAP on biocompatibility, surface improvement, and cleaning efficacy were found in the literature. Among these studies, only Matthes et al [31] assessed the effects of a combined biofilm removal with an optimized AA with erythritol powder and an argon CAP on osteoblast-like cells spreading.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies have been published in the literature on the effects of a combined treatment of CAP with other devices. In a recent review [18], only 17 in vitro studies and 5 in vivo on animal models investigating the effects of CAP on biocompatibility, surface improvement, and cleaning efficacy were found in the literature. Among these studies, only Matthes et al [31] assessed the effects of a combined biofilm removal with an optimized AA with erythritol powder and an argon CAP on osteoblast-like cells spreading.…”
Section: Discussionmentioning
confidence: 99%
“…Cold atmospheric plasma (CAP) is an innovative, yet earlystage, treatment modality in the oral implantology field. In a recent review [18] based on 23 studies investigating the effects of CAP on biocompatibility, surface improvement, and cleaning efficacy of implant surfaces, it was suggested that CAP is a promising option for the treatment of periimplantitis [19,20], although further evidence is necessary to draw final conclusions. The hypothesized benefits in incorporating CAP for peri-implantitis treatment is that it can act via a liquid medium.…”
Section: Introductionmentioning
confidence: 99%
“…Various innovative strategies using laser, photodynamic therapy, and ozone (O 3 ) as well as cold atmospheric plasma (CAP) treatment have emerged to provide a stable debridement procedure that seeks to meet all necessary criteria for periodontal healing [17][18][19][20]. Cold atmospheric plasma is a highly reactive gas that has been described to generate a variety of reactive species (ozone, reactive oxygen, and nitrogen species) with antimicrobial effects [21]. Although the precise mode of action is still under investigation, similar efficacy to the effect of 0.2% chlorhexidine digluconat could be observed in bacterial biofilms [22].…”
Section: Introductionmentioning
confidence: 99%
“…By altering the surface roughness and wettability, plasma therapy can improve cell adhesion. Plasma therapy lowers the contact angle and supports the spread of osteoblastic cells in chairside operations using NTAPP prior to implant placement [12,13].…”
Section: Modification Of the Implant Surface To Improve Osseointegrationmentioning
confidence: 98%